KUALITAS TIDUR IBU DAN PRAKTIK PEMBERIAN ASI: PERBANDINGAN PENILAIAN SUBJEKTIF DAN PITTSBURGH SLEEP QUALITY INDEX (PSQI) - Siska Febrina Fauziah; Viqy Lestaluhu (Poltekkes Kemenkes Maluku, 2026)
The postpartum period poses significant risks to sleep quality disruption, particularly among breastfeeding mothers who simultaneously face the demands of infant feeding, domestic work, and caregiving responsibilities. Poor sleep quality may affect the success of exclusive breastfeeding; however, evidence on this relationship remains inconsistent in the literature, partly due to differences in sleep quality measurement methods. This study aimed to analyze the association between subjective sleep quality and sleep quality based on the Pittsburgh Sleep Quality Index (PSQI) score with breastfeeding practices. A cross-sectional design was employed involving 214 mothers with children aged 0–2 years recruited through social media. Data were collected via an online questionnaire comprising subjective sleep quality assessment, PSQI, and breastfeeding practice measures. The majority of respondents perceived their sleep quality as fairly good (71.0%); however, based on PSQI scores, most had poor sleep quality (79.0%). Exclusive breastfeeding was reported by 74.8% of respondents. Chi-square analysis revealed no statistically significant association between subjective sleep quality and breastfeeding practices (p=0.509), nor between PSQI-based sleep quality and breastfeeding practices (p=0.061). Nevertheless, mothers with good sleep quality based on PSQI scores showed a higher tendency toward exclusive breastfeeding. A discrepancy exists between subjective sleep quality perception and structured sleep quality assessment using the PSQI. The PSQI is recommended for routine maternal sleep screening as it provides a more comprehensive and objective assessment compared to subjective perception alone.